Sustainable Corrosion Inhibitors from Pharmaceutical Wastes: Advancing Energy-Efficient Chemistry with Green Solutions - Narasimha Raghavendra; Sharanappa Chapi; Murugendrappa M. V.; Małgorzata Pawlak; Mohammad Reza Saeb (Energies)
Pharmaceutical waste is a type of bio-waste inevitably generated by the pharmaceutical industry, often due to regulatory changes, product deterioration, or expiration. However, their collection and valorization can be approached from a sustainable perspective, offering potential energy-efficient solutions. In this work, the expired Eslicarbazepine acetate drug (ESLD) was utilized as a sustainable anticorrosive agent against mild steel in a 3 M HCl wash solution. Experimental tests combined with theoretical Density Functional Theory (DFT) and Monte Carlo (MC) simulations revealed the corrosion inhibition potential of ESLD. The gasometrical results revealed a high inhibition efficiency rate of 98% upon increases in concentration of expired ESLD from 0.25 to 1.00 mg·L−1, whereas hydrogen gas evolution decreased to 0.7 mL. An impedance investigation evidenced the pivotal role of charge transfer in reducing the disintegration process. As per DFT computations and MC simulation, electron-rich elements in the expired ESLD were key in controlling the dissolution through the adsorption process. Contact angle studies revealed that the increment in the contact angle from 61° to 80° in the presence of expired ESLD validates the chemical, electrochemical, and computational results. This approach not only mitigates pharmaceutical pollution, but also exemplifies the integration of green chemistry principles into corrosion protection, contributing to energy-efficient and sustainable industrial practices.